Erythrocyte sedimentation rate in diabetic and non-diabetic patients of cardiovascular disease - Kiyani, Mubin Mustafa; Jahan, Saira; Kiyani, Sania Khawar; Rehman, Hamza; Khan, Lal Gul; Iqbal, Umar (Jurnal Teknologi Laboratorium, 2019)
The pervasiveness of global endemic of type II diabetes, driven by population development, increasing obesity, urbanization, and other additional unidentified factors may be crumpled in the next 20yrs. The purpose of this study was to determine the correlation of ESR in diabetic and non-diabetic patients of cardiovascular diseases. It is a co-relational study conducted at KRL hospital Islamabad from February 2018 to September 2018. The study population compromised a total of 180 cases aged 45 to 50 years were taken, in which 60 cases of CVD with DM, 60 cases of CVD without DM and 60 normal healthy population were taken. All patients and controls gave written informed consent. All subjects went through a general physical examination, and a questionnaire was used to collect the records about demographics and past medical history and existing use of medications. In the presented study, Pearson's Correlation between ESR of healthy and ESR of CVD without DM shows a weak correlation between these two variables i.e., 0.127 with a p-value of 0.503. We also establish that there is a direct intermediate relationship between ESR of healthy and ESR of CVD with DM. High level of ESR in CVD patients might indicate the prognosis of DM. To confirm this further researches and studies must be conducted in this area